Method for producing high-purity zinc sulfide by using sodium hydrosulfide
By reactoring sodium sulfide and zinc oxide under alkaline conditions, compound decomposition reactions, prepare high -purity zinc sulfide, and solve the use of sodium hydroxide in sodium sulfide solution to solve the decline in the purity of zinc sulfide in existing technologies and waste of resources in resources. The problem has achieved zinc -sulfide preparation and zero emissions of efficient, economical.
Patent Information
- Application Number
- CN202411402916.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-24
Smart Images

Figure CN119349625A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of by-product resource utilization, and specifically relates to a method for producing high-purity zinc sulfide by utilizing sodium hydrosulfide, and in particular to a method for producing high-purity zinc sulfide by utilizing sodium hydrosulfide produced as a by-product of chemical fiber. Background Art
[0002] At present, chemical fiber enterprises use sodium hydroxide aqueous solution to absorb and dissolve hydrogen sulfide waste gas. This method uses sodium hydroxide aqueous solution equivalent to 10,000 tons of sodium hydroxide to absorb hydrogen sulfide waste gas, and produces about 30,000 cubic meters of sodium hydrosulfide waste liquid. This method not only wastes a large amount of sodium hydroxide aqueous solution, but also the sodium hydrosulfide solution produced has a low selling value. Therefore, a new process is urgently needed to recycle the wasted sodium hydroxide aqueous solution and convert the low value-added product (sodium hydrosulfide solution) into a high value-added product, so as to achieve energy saving, consumption reduction, and zero emission.
[0003] At present, the relevant research and development of zinc sulfide preparation at home and abroad mainly has the following technical problems: Chinese invention patent CN113104883B discloses a method for preparing zinc sulfide using industrial-grade zinc sulfate and sodium sulfide as raw materials, but the method needs to be complicated after impurity removal and purification before reaction, the cost is high, and the method can only be carried out in a small-scale test in the laboratory, and cannot be mass-produced. Chinese invention patent CN103288123B discloses a method for preparing zinc sulfide using zinc oxide, sulfuric acid and sodium sulfide as raw materials, but the calcination temperature of zinc sulfide in this method is 745-755°C. According to thermogravimetric analysis, a part of zinc sulfide will be decomposed by high temperature at about 650°C, and impurities will be generated to reduce the purity of zinc sulfide. Therefore, this method will cause the purity of the prepared zinc sulfide product to decrease.
[0004] At present, the research on the preparation process of high-purity zinc sulfide is mostly in the laboratory stage, which is not enough for large-scale production. The high-purity zinc sulfide currently used in my country is all imported products, and the technology is monopolized by foreign countries. Therefore, it is of great significance to develop a production method of high-purity zinc sulfide that is suitable for large-scale production and economically feasible. Summary of the invention
[0005] In view of the above problems, the present invention provides a method for producing high-purity zinc sulfide by utilizing sodium hydrosulfide.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is:
[0007] A method for producing high-purity zinc sulfide by using sodium hydrosulfide, wherein the method comprises carrying out a double decomposition reaction of sodium hydrosulfide and zinc oxide under alkaline conditions, filtering / centrifuging after the reaction is completed, and purifying and calcining the obtained zinc sulfide filter cake to obtain a high-purity zinc sulfide finished product.
[0008] Furthermore, the filtrate from filtration / centrifugation and the washing liquid from the purification process are returned to the pulp pressing step or the sulfur-containing waste gas absorption step in the chemical fiber process according to different alkali concentrations.
[0009] Furthermore, the specific process of the method includes the following steps:
[0010] S1. Dissolve zinc oxide in sodium hydroxide aqueous solution to react and generate sodium zincate solution
[0011] S2, adding sodium hydroxide to the sodium hydrosulfide solution to obtain an alkaline sodium sulfide solution;
[0012] S3, sodium zincate solution and alkaline sodium sulfide solution are added to the reactor to carry out double decomposition reaction. After the reaction is completed, a slurry is obtained; wherein the slurry includes zinc sulfide precipitate;
[0013] The specific double decomposition reaction is as follows:
[0014] ZnO+2NaOH=Na2ZnO2+H2O;
[0015] NaHS+NaOH=Na2S+H2O;
[0016] Na2ZnO2+Na2S+2H2O=ZnS+4NaOH;
[0017] S4. After the reaction is completed, the obtained slurry is filtered / centrifuged to obtain a zinc sulfide filter cake and a filtrate;
[0018] Filtration refers to the filtration of micron-sized zinc sulfide crystals through a Buchner funnel and medium-speed filter paper. Plate and frame filtration is used in industrial production. Centrifugation refers to the separation of nano-sized zinc sulfide crystals through high-speed centrifuge centrifugation to separate zinc sulfide filter cake and filtrate.
[0019] The zinc sulfide filter cake is firstly alkali-washed with a sodium hydroxide aqueous solution and then washed with clean water to obtain a zinc sulfide crude product, an alkali washing solution and a water washing solution;
[0020] After the carbonate is removed by calcium hydroxide, part of the filtrate and the alkaline washing liquid is returned to the pulp pressing step in the chemical fiber process, and the other part is returned to step S1 to replace the sodium hydroxide aqueous solution as the reaction solvent to dissolve zinc oxide;
[0021] After the washing liquid is recovered, it is returned to the chemical fiber sulfur-containing waste gas absorption process to be used for chemical fiber to absorb hydrogen sulfide waste gas and prepare sodium hydrosulfide solution.
[0022] The crude zinc sulfide is dried, placed in a tubular furnace, calcined under nitrogen protection, and then ground to form zinc sulfide (i.e., finished zinc sulfide).
[0023] Further, in step S1, the concentration of the sodium hydroxide aqueous solution is 25-32 wt %;
[0024] In step S2, the sum of the amount of sodium hydroxide added to the sodium hydrosulfide solution and the sodium hydroxide released by the double decomposition reaction of sodium hydrosulfide and sodium zincate in step S3, with respect to the total mass of the sodium hydrosulfide solution, is 25-32 wt%.
[0025] Furthermore, in step S1, the mass percentage of industrial-grade zinc oxide in the sodium hydroxide aqueous solution is 8-9wt%.
[0026] Furthermore, in step S2, the sodium hydrosulfide solution is a treatment solution of hydrogen sulfide waste gas produced as a byproduct in a chemical fiber process, wherein the concentration of sodium hydrosulfide is 190-210 g / L.
[0027] Furthermore, step S3 is a controllable crystallization technology, and the particle size of zinc sulfide can be controlled to be in the micrometer or nanometer level;
[0028] The particle size of zinc sulfide is controlled to be micron-sized by step S3; when the particle size of zinc sulfide is micron-sized, in step S3, the reactor is a hydrothermal reactor;
[0029] The sodium zincate solution and the alkaline sodium sulfide solution are added into the reactor by double dropwise addition;
[0030] The molar ratio of sodium zincate in the sodium zincate solution to sodium sulfide in the alkaline sodium sulfide solution is 1:1 to 1:1.03;
[0031] After adding the sodium zincate solution and the alkaline sodium sulfide solution and before the double decomposition reaction, 11 to 30 wt% of the calculated zinc sulfide precipitate mass is added as a seed crystal;
[0032] The double drop addition time is 30 to 60 minutes;
[0033] The double decomposition reaction is carried out at a stirring speed of 200 to 300 r / min, a temperature of 60 to 80° C., and a time of more than 4 hours.
[0034] Furthermore, the particle size of zinc sulfide is controlled to be nanometer-level through step S3; when the particle size of zinc sulfide is nanometer-level, in step S3, the reactor is selected as a Y-type microchannel reactor;
[0035] The Y-shaped microchannel reactor comprises a reaction chamber, a left feed pipe and a right feed pipe connected to the reaction chamber are fixed on the top of the reaction chamber in an inclined manner, and the left feed pipe and the right feed pipe are symmetrically arranged;
[0036] The length of the left and right feed pipes is 280±2cm and the diameter is 1850±5μm;
[0037] The Y-shaped angle between the left feed pipe and the right feed pipe is 60° to 90°;
[0038] The total flow rate of adding sodium zincate solution and alkaline sodium sulfide solution is 3-5 mL / min, and the materials are added in a way of impacting the inflowing materials, and the pressure is 2-2.5 MPa;
[0039] The temperature of the double decomposition reaction is 60-80°C;
[0040] The molar ratio of sodium zincate in the sodium zincate solution to sodium sulfide in the alkaline sodium sulfide solution is 1:1 to 1:1.03.
[0041] Further, in step S4, during the alkali washing process, the amount of sodium hydroxide aqueous solution used is 1 to 1.5 times the volume of the filtrate, the concentration is 25 to 32 wt%, and the number of alkali washings is once;
[0042] During the water washing process, the amount of clean water used is 10 to 12 times the volume of the filtrate, and the number of water washings is twice.
[0043] Furthermore, in step S1, the reaction temperature is 60-80°C and the stirring speed is 200-300 r / min;
[0044] In step S4, drying is first performed at 60-85°C under vacuum for 1.5-2h, and then the temperature is raised to 110-120°C and dried for 1.5-2h;
[0045] Calcination is carried out under nitrogen protection at 400-600°C for 2-4 hours.
[0046] The beneficial effects of the method for producing high-purity zinc sulfide by utilizing sodium hydrosulfide of the present invention are:
[0047] The invention uses sodium hydrosulfide solution (i.e., hydrogen sulfide waste gas treatment liquid of a chemical fiber company), which is a byproduct of chemical fiber process production, as a sulfur source and industrial-grade zinc oxide as a zinc source to produce zinc sulfide, and a part of the filtrate obtained by filtering and an alkali washing liquid is used as a reaction solvent to participate in the reaction, and the other part is returned to the pulp porridge liquid pressing process in the chemical fiber process, and the washing liquid is returned to the chemical fiber sulfur-containing waste gas absorption process to be used for chemical fiber to absorb hydrogen sulfide waste gas and prepare sodium hydrosulfide solution. The whole process realizes the recovery and recycling of sodium hydroxide in the sodium hydrosulfide solution, and converts a low value-added product (sodium hydrosulfide solution) into a high value-added product (high-purity zinc sulfide), and truly realizes zero emission, with significant economic and social benefits.
[0048] In the calcination of zinc sulfide, the thermogravimetric data was used to conduct analytical experiments to determine the calcination temperature of zinc sulfide, further improving the purity of the finished zinc sulfide product.
[0049] The invention uses industrial-grade zinc oxide and industrial-grade sodium hydrosulfide as raw materials and cooperates with various industrial equipment to solve the long-standing problem that zinc sulfide can only be studied in laboratories but cannot be used for industrial mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 It is a schematic structural diagram of a Y-type microchannel reactor used in the present invention;
[0051] Figure 2 is an XRD analysis diagram of the zinc sulfide product prepared in Example 1 of the present invention;
[0052] Figure 3 It is a comparison diagram of the EDS characterization spectra of the Sahaliben zinc sulfide in Example 1 of the present invention and the finished zinc sulfide prepared by the present invention; wherein the left figure is the EDS characterization spectrum of the Sahaliben zinc sulfide, and the right figure is the EDS characterization spectrum of the finished zinc sulfide prepared in Example 1;
[0053] In the figure, 1. left feed pipe; 2. right feed pipe; 3. reaction chamber; 4. anti-high pressure component. DETAILED DESCRIPTION
[0054] The technical solutions in the embodiments of the present invention are described clearly and completely below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention can also be implemented in other ways different from those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0055] A method for producing high-purity zinc sulfide by utilizing sodium hydrosulfide of the present invention comprises the following steps:
[0056] S1. Dissolve industrial-grade zinc oxide in a sodium hydroxide aqueous solution with a concentration of 25-32wt%, and stir the mixture for 0.5h at a temperature of 60-80°C and a stirring speed of 200-300r / min to generate a sodium zincate solution, which is used as one of the reactants for generating zinc sulfide; wherein the mass percentage of the industrial-grade zinc oxide in the sodium hydroxide aqueous solution is 8-9wt%;
[0057] S2, adding sodium hydroxide solid to the sodium hydrosulfide solution to maintain a high alkaline environment to obtain an alkaline sodium sulfide solution;
[0058] Among them, sodium hydrosulfide solution is a by-product hydrogen sulfide waste gas treatment solution in the chemical fiber process, in which the sodium hydrosulfide concentration is 190-210g / L;
[0059] The sum of the amount of sodium hydroxide added to the sodium hydrosulfide solution and the sodium hydroxide released by the double decomposition reaction between sodium hydrosulfide and sodium zincate in step S3, and the percentage of the total mass of the sodium hydrosulfide solution is 25-32wt%, thereby ensuring that the concentration of sodium hydroxide in the entire double decomposition reaction system is always maintained at 25-32wt%, preventing the generation of zinc carbonate in the entire double decomposition system, and subsequently obtaining an alkali solution (i.e., the filtrate in step S4) by filtering / centrifugation, thereby realizing the recovery of sodium hydroxide in the sodium hydrosulfide solution (i.e., the by-product hydrogen sulfide waste gas treatment liquid in the chemical fiber process), thereby realizing the recycling of sodium hydroxide (that is, the sodium ions of sodium hydrosulfide in the by-product hydrogen sulfide waste gas treatment liquid in the chemical fiber process are converted into sodium hydroxide, thereby realizing the recovery of sodium hydroxide);
[0060] For example, when the sodium hydrosulfide concentration in the sodium hydrosulfide solution is 202 g / L, the amount of sodium hydroxide solid added per liter of sodium hydrosulfide solution is 184-234 g / L;
[0061] S3. This step is a controllable crystallization technology, which can control the particle size of the final prepared zinc sulfide to be micrometer or nanometer level.
[0062] When preparing micron-sized zinc sulfide, under the control of a peristaltic metering pump, the sodium zincate in the sodium zincate solution and the sodium sulfide in the alkaline sodium sulfide solution are directly added dropwise from the feed port in a double-dropping manner according to a molar ratio of 1:1 to 1:1.03, and the double-dropping time of the sodium zincate solution and the alkaline sodium sulfide solution added to the common hydrothermal reactor is adjusted by controlling the flow rates of the sodium zincate solution and the alkaline sodium sulfide solution, the double-dropping time is 30 to 60 minutes, and a stable temperature of 60 to 80° C. and a stirring speed of 200 to 300 r / min are maintained, and 11 to 30 wt% of the calculated mass of the zinc sulfide precipitate (Sahaliben zinc sulfide) is added as a seed crystal, and a double decomposition reaction is carried out for more than 4 hours. After the reaction is completed, a slurry (the slurry includes zinc sulfide precipitate and alkali solution) is obtained;
[0063] When preparing nano-sized zinc sulfide, the sodium zincate solution and the alkaline sodium sulfide solution are added to a Y-shaped microchannel reactor in a molar ratio of 1:1 to 1:1.03, and the flow rates of both streams are 3 to 5 mL / min. The feed is added in a manner of impacting the inflowing material, the pressure is 2 to 2.5 MPa, and the double decomposition reaction is carried out at 60 to 80° C. for more than 4 hours. After the reaction is completed, a slurry (including zinc sulfide precipitate and alkali solution) is obtained;
[0064] Among them, the structure of the Y-type microchannel reactor is as follows Figure 1As shown, it is the same as the conventional Y-type microchannel reactor, including a reaction chamber 3, the top of which is tiltedly fixed with a left feed pipe 1 and a right feed pipe 2 connected to the reaction chamber 3, and the left feed pipe 1 and the right feed pipe 2 are symmetrically arranged; the top of the reaction chamber 3 is fixed with an anti-high pressure assembly 4, and the bottom of the reaction chamber 3 is fixed with a discharge pipe connected to the reaction chamber 3. The only improvement is that the length of the left feed pipe 1 and the right feed pipe 2 of the Y-type microchannel reactor of the present invention are both 280±2cm, the diameter is both 1850±5μm, and the Y-type angle between the left feed pipe 1 and the right feed pipe 2 is 60° to 90°. Sodium zincate solution and alkaline sodium sulfide solution are added to the Y-type microchannel reactor from the left feed pipe 1 and the right feed pipe 2 respectively.
[0065] The specific double decomposition reaction is as follows:
[0066] ZnO+2NaOH=Na2ZnO2+H2O;
[0067] NaHS+NaOH=Na2S+H2O;
[0068] Na2ZnO2+Na2S+2H2O=ZnS+4NaOH;
[0069] S4. After the reaction is completed, the obtained slurry is filtered / centrifuged to obtain a zinc sulfide filter cake and a filtrate;
[0070] Filtration refers to the filtration of micron-sized zinc sulfide crystals (i.e. zinc sulfide precipitates) through a Buchner funnel and medium-speed filter paper. Plate and frame filtration is used in industrial production. Centrifugation refers to the separation of nano-sized zinc sulfide crystals (i.e. zinc sulfide precipitates) through high-speed centrifuge centrifugal stratification to separate zinc sulfide filter cake and filtrate.
[0071] The zinc sulfide filter cake is firstly alkali-washed once with a sodium hydroxide aqueous solution having a concentration of 25 to 32 wt% and 1 to 1.5 times the volume of the filtrate, and then washed twice with clean water having a volume of 10 to 12 times the volume of the filtrate to obtain a zinc sulfide crude product, an alkali washing solution and a water washing solution;
[0072] The purpose of washing with sodium hydroxide aqueous solution is to remove zinc carbonate and zinc hydroxide impurities on the surface of zinc sulfide, and the purpose of washing with clean water is to wash away the alkalinity in the zinc sulfide filter cake.
[0073] After the carbonate is removed from the filtrate and the alkaline washing liquid by calcium hydroxide, they fully meet the standards for chemical fiber pulp pressing liquid (wherein the hydroxide concentration is 5.5-7 mol / L). One part is returned to the pulp pressing liquid process in the chemical fiber process, and the other part is returned to step S1 to replace the sodium hydroxide aqueous solution as the reaction solvent to dissolve zinc oxide.
[0074] After the washing liquid (containing a hydroxide concentration of 2.5 to 3 mol / L) is recovered, it is returned to the chemical fiber sulfur-containing waste gas absorption process to be used for chemical fiber absorption of hydrogen sulfide waste gas and preparation of sodium hydrosulfide solution, thereby achieving alkali solution recycling and zero emission in the entire process.
[0075] The crude zinc sulfide is vacuum dried at 60-85°C for 1.5-2h, then heated to 110-120°C and dried for 1.5-2h, then placed in a tubular furnace, calcined at 400-600°C for 2-4h under nitrogen protection, and then ground to form a finished zinc sulfide product; wherein, the calcination temperature is determined by the analysis of the thermogravimetric results. As shown in the figure, the thermogravimetric results of zinc sulfide show that a peak is generated near 650°C, indicating that zinc sulfide is decomposed into other substances at 650°C, so the calcination temperature is determined to be 400-600°C.
[0076] Example 1 A method for producing high-purity zinc sulfide using sodium hydrosulfide
[0077] This embodiment is a method for producing high-purity zinc sulfide using sodium hydrosulfide, and preparing micron-sized zinc sulfide, comprising the following steps:
[0078] S1. Dissolve industrial-grade zinc oxide in a 32wt% sodium hydroxide aqueous solution, stir and react at 80°C and 300r / min for 0.5h to generate a sodium zincate solution, wherein the mass percentage of the industrial-grade zinc oxide in the sodium hydroxide aqueous solution is 9wt%.
[0079] S2. In a sodium hydrosulfide solution with a concentration of 202 g / L, 234 g of sodium hydroxide solid is added per liter of sodium hydrosulfide solution to maintain a high alkaline environment to obtain an alkaline sodium sulfide solution. The sodium hydrosulfide solution is a by-product hydrogen sulfide waste gas treatment solution in the chemical fiber process.
[0080] S3. Under the control of a peristaltic metering pump, the sodium zincate in the sodium zincate solution and the sodium sulfide in the alkaline sodium sulfide solution are added to an ordinary hydrothermal reactor in a double-drop manner in a molar ratio of 1:1.03. The double-dropping time is 60 minutes, and the temperature is maintained at 80°C and the stirring speed is 300 r / min. A zinc sulfide product (Sahaliben zinc sulfide) of 20 wt% of the calculated mass of the zinc sulfide precipitate is added as a seed crystal, and a double decomposition reaction is carried out for 4 hours. After the reaction is completed, a slurry (the slurry includes zinc sulfide precipitate and alkali solution) is obtained.
[0081] S4. After the reaction is completed, the obtained slurry is filtered through a plate and frame to obtain a zinc sulfide filter cake and a filtrate;
[0082] The zinc sulfide filter cake is firstly alkali washed once with a 32wt% sodium hydroxide aqueous solution of 1.5 times the volume of the filtrate, and then washed twice with clean water of 12 times the volume of the filtrate to obtain a zinc sulfide crude product, an alkali washing solution and a water washing solution;
[0083] After the carbonate is removed from the filtrate and the alkaline washing liquid by calcium hydroxide, they fully meet the chemical fiber pressing liquid standard (wherein the hydroxide concentration is 7 mol / L). One part is returned to the pulp pressing liquid process in the chemical fiber process, and the other part is returned to step S1 to replace the sodium hydroxide aqueous solution as the reaction solvent to dissolve zinc oxide.
[0084] After the washing liquid (containing a hydroxide concentration of 3 mol / L) is recovered, it is returned to the chemical fiber sulfur-containing waste gas absorption process to be used for chemical fiber to absorb hydrogen sulfide waste gas and prepare sodium hydrosulfide solution, thereby realizing the recycling of alkali solution and zero emission of the entire process.
[0085] The crude zinc sulfide was vacuum dried at 80°C for 2h, then heated to 120°C and dried for 2h, then placed in a tubular furnace, calcined at 400°C for 4h under nitrogen protection, and then ground to form a finished zinc sulfide product with a purity of 98%.
[0086] The obtained zinc sulfide product was further characterized by XRD and EDS, and compared with the Shahaliben zinc sulfide sample. The specific results are shown in Figures 2 to 3 and Table 1. Among them, Figure 2 is the XRD analysis diagram of the zinc sulfide product prepared in this embodiment, Figure 3 It is a comparison chart of EDS characterization spectra of Sahaliben zinc sulfate (left picture) and the finished zinc sulfide prepared in this example (right picture).
[0087] Table 1 Atomic ratios of the zinc sulfide sample and the finished zinc sulfide prepared in this embodiment
[0088]
[0089]
[0090] Depend on Figure 2 It can be proved that the finished zinc sulfide product prepared in this embodiment is completely consistent with the zinc sulfide standard card #36-1450 (i.e., the X-ray powder diffraction standard card of zinc sulfide, numbered 36-1450); Figure 3 It can be seen from the EDS results in Table 1 that the Zn:S (atomic ratio) of the zinc sulfide product prepared in this embodiment is 1:1, while the Zn:S (atomic ratio) in the Sahaliben zinc sulfide sample is 1:0.89, indicating that the purity of the zinc sulfide product prepared in this embodiment is better than that of the Sahaliben zinc sulfide sample, that is, the purity of the zinc sulfide prepared by the present invention is even better than the pure zinc sulfide sold on the market.
[0091] Example 2 A method for producing high-purity zinc sulfide using sodium hydrosulfide
[0092] This embodiment is a method for producing high-purity zinc sulfide using sodium hydrosulfide, and preparing nano-grade zinc sulfide, comprising the following steps:
[0093] S1. Dissolve industrial-grade zinc oxide in a 25wt% sodium hydroxide aqueous solution, stir and react at 80°C and 200r / min for 0.5h to generate a sodium zincate solution, wherein the mass percentage of the industrial-grade zinc oxide in the sodium hydroxide aqueous solution is 8wt%.
[0094] S2. Add 220g of solid sodium hydroxide per liter of sodium hydrosulfide solution to a sodium hydrosulfide solution with a concentration of 210g / L, maintain a high alkaline environment, and obtain an alkaline sodium sulfide solution. The sodium hydrosulfide solution is a by-product hydrogen sulfide waste gas treatment solution in the chemical fiber process.
[0095] S3. Under the control of a peristaltic metering pump, the molar ratio of sodium zincate in the sodium zincate solution to sodium sulfide in the alkaline sodium sulfide solution is 1:1, and the flow rates of both streams are 5 mL / min. The streams are added into a Y-type microchannel reactor in the form of impact inflow, and a double decomposition reaction is carried out at 80° C. and 2.5 MPa to obtain a slurry (the slurry includes zinc sulfide precipitate and alkali solution); wherein, the length of the left feed pipe 1 and the right feed pipe 2 of the Y-type microchannel reactor are both 282 cm, the diameter is both 1855 μm, and the Y-type angle between the left feed pipe 1 and the right feed pipe 2 is 90°.
[0096] S4. After the reaction is completed, the obtained slurry is centrifuged and separated by high-speed centrifuge to obtain zinc sulfide filter cake and filtrate;
[0097] The zinc sulfide filter cake is firstly alkaline washed once with a 25wt% sodium hydroxide aqueous solution of 1.5 times the volume of the filtrate, and then washed twice with clean water of 12 times the volume of the filtrate to obtain a zinc sulfide crude product, an alkaline washing solution and a water washing solution;
[0098] After the carbonate is removed from the filtrate and the alkaline washing liquid by calcium hydroxide, they fully meet the chemical fiber pressing liquid standard (wherein the hydroxide concentration is 6.8 mol / L). One part is returned to the pulp pressing liquid step in the chemical fiber process, and the other part is returned to step S1 to replace the sodium hydroxide aqueous solution as the reaction solvent to dissolve zinc oxide.
[0099] After the washing liquid (containing a hydroxide concentration of 2.9 mol / L) is recovered, it is returned to the chemical fiber sulfur-containing waste gas absorption process to be used for chemical fiber absorption of hydrogen sulfide waste gas and preparation of sodium hydrosulfide solution, thereby achieving alkali solution recycling and zero emission in the entire process.
[0100] The crude zinc sulfide was vacuum dried at 60°C for 1.5h, then heated to 110°C and dried for 1.8h, then placed in a tubular furnace, calcined at 400°C for 4h under nitrogen protection, and then ground to form a finished zinc sulfide product with a purity of 99%.
[0101] Example 3 A method for producing high-purity zinc sulfide using sodium hydrosulfide
[0102] This embodiment is a method for producing high-purity zinc sulfide using sodium hydrosulfide, and preparing micron-sized zinc sulfide, comprising the following steps:
[0103] S1. Dissolve industrial-grade zinc oxide in a 30wt% sodium hydroxide aqueous solution, stir and react at 60°C and 250r / min for 0.5h to generate a sodium zincate solution, wherein the mass percentage of the industrial-grade zinc oxide in the sodium hydroxide aqueous solution is 8.5wt%.
[0104] S2. In a sodium hydrosulfide solution with a concentration of 190 g / L, 203 g of sodium hydroxide solid is added per liter of sodium hydrosulfide solution to maintain a high alkaline environment to obtain an alkaline sodium sulfide solution. The sodium hydrosulfide solution is a by-product hydrogen sulfide waste gas treatment solution in the chemical fiber process.
[0105] S3. Under the control of a peristaltic metering pump, the sodium zincate in the sodium zincate solution and the sodium sulfide in the alkaline sodium sulfide solution are added to an ordinary hydrothermal reactor in a double-dropping manner in a molar ratio of 1:1. The double-dropping time is 45 minutes, and the temperature is maintained at 60°C and the stirring speed is 250 r / min. 11 wt% of the calculated mass of the zinc sulfide precipitate (Sahaliben zinc sulfide) is added as a seed crystal, and a double decomposition reaction is carried out for 5 hours. After the reaction is completed, a slurry (the slurry includes zinc sulfide precipitate and alkali solution) is obtained.
[0106] S4. After the reaction is completed, the obtained slurry is filtered through a plate and frame to obtain a zinc sulfide filter cake and a filtrate;
[0107] The zinc sulfide filter cake is firstly alkali-washed once with a 30wt% sodium hydroxide aqueous solution of 1.2 times the volume of the filtrate, and then washed twice with clean water of 10 times the volume of the filtrate to obtain a zinc sulfide crude product, an alkali washing solution and a water washing solution;
[0108] After the carbonate is removed from the filtrate and the alkaline washing liquid by calcium hydroxide, they fully meet the chemical fiber pressing liquid standard (wherein the hydroxide concentration is 6.5 mol / L). One part is returned to the pulp pressing liquid process in the chemical fiber process, and the other part is returned to step S1 to replace the sodium hydroxide aqueous solution as the reaction solvent to dissolve zinc oxide.
[0109] After the washing liquid (containing a hydroxide concentration of 2.8 mol / L) is recovered, it is returned to the chemical fiber sulfur-containing waste gas absorption process to be used for chemical fiber to absorb hydrogen sulfide waste gas and prepare sodium hydrosulfide solution, thereby realizing the recycling of alkali solution and zero emission of the entire process.
[0110] The crude zinc sulfide was vacuum dried at 70°C for 1.8h, then heated to 115°C and dried for 1.5h, then placed in a tubular furnace, calcined at 600°C for 4h under nitrogen protection, and then ground to form a finished zinc sulfide product with a purity of 95%.
[0111] Example 4 A method for producing high-purity zinc sulfide using sodium hydrosulfide
[0112] This embodiment is a method for producing high-purity zinc sulfide using sodium hydrosulfide, comprising the following steps:
[0113] S1. Dissolve industrial-grade zinc oxide in a 32wt% sodium hydroxide aqueous solution, stir and react at 80°C and 300r / min for 0.5h to generate a sodium zincate solution, wherein the mass percentage of the industrial-grade zinc oxide in the sodium hydroxide aqueous solution is 8wt%.
[0114] S2. In a sodium hydrosulfide solution with a concentration of 202 g / L, 234 g of sodium hydroxide solid is added per liter of sodium hydrosulfide solution to maintain a high alkaline environment to obtain an alkaline sodium sulfide solution. The sodium hydrosulfide solution is a by-product hydrogen sulfide waste gas treatment solution in the chemical fiber process.
[0115] S3. Under the control of a peristaltic metering pump, the sodium zincate in the sodium zincate solution and the sodium sulfide in the alkaline sodium sulfide solution are added to an ordinary hydrothermal reactor in a double-drop manner in a molar ratio of 1:1.03. The double-dropping time is 60 minutes, and the temperature is maintained at 60°C and the stirring speed is 200 r / min. 30 wt% of the calculated mass of the zinc sulfide precipitate (Sahaliben zinc sulfide) is added as a seed crystal, and a double decomposition reaction is carried out for 4 hours. After the reaction is completed, a slurry (the slurry includes zinc sulfide precipitate and alkali solution) is obtained.
[0116] S4. After the reaction is completed, the obtained slurry is filtered through a plate and frame to obtain a zinc sulfide filter cake and a filtrate;
[0117] The zinc sulfide filter cake is firstly alkaline washed once with a sodium hydroxide aqueous solution having a concentration of 32 wt% by volume of 1 times the filtrate, and then washed twice with clean water having a volume of 12 times the filtrate, to obtain a zinc sulfide crude product, an alkaline washing solution and a water washing solution;
[0118] After the carbonate is removed from the filtrate and the alkaline washing liquid by calcium hydroxide, they fully meet the chemical fiber pressing liquid standard (wherein the hydroxide concentration is 7 mol / L). One part is returned to the pulp pressing liquid process in the chemical fiber process, and the other part is returned to step S1 to replace the sodium hydroxide aqueous solution as the reaction solvent to dissolve zinc oxide.
[0119] After the washing liquid (containing a hydroxide concentration of 3 mol / L) is recovered, it is returned to the chemical fiber sulfur-containing waste gas absorption process to be used for chemical fiber to absorb hydrogen sulfide waste gas and prepare sodium hydrosulfide solution, thereby realizing the recycling of alkali solution and zero emission of the entire process.
[0120] The crude zinc sulfide was vacuum dried at 80°C for 2h, then heated to 120°C and dried for 2h, then placed in a tubular furnace, calcined at 400°C for 4h under nitrogen protection, and then ground to form a finished zinc sulfide product with a purity of 95%.
[0121] Example 5 A method for producing high-purity zinc sulfide using sodium hydrosulfide
[0122] S1. Dissolve industrial-grade zinc oxide in a 28 wt % sodium hydroxide aqueous solution, stir and react at 70° C. and 300 r / min for 0.5 h to generate a sodium zincate solution, wherein the mass percentage of the industrial-grade zinc oxide in the sodium hydroxide aqueous solution is 8.5 wt %.
[0123] S2. In a sodium hydrosulfide solution with a concentration of 200 g / L, 220 g of sodium hydroxide solid is added per liter of sodium hydrosulfide solution to maintain a high alkaline environment to obtain an alkaline sodium sulfide solution. The sodium hydrosulfide solution is a by-product hydrogen sulfide waste gas treatment solution in the chemical fiber process.
[0124] S3. Under the control of a peristaltic metering pump, the sodium zincate in the sodium zincate solution and the sodium sulfide in the alkaline sodium sulfide solution are added to an ordinary hydrothermal reactor in a double-drop manner in a molar ratio of 1:1.02. The double-dropping time is 30 minutes, and the temperature is maintained at 70°C and the stirring speed is 250r / min. A zinc sulfide product (Sahaliben zinc sulfide) of 25wt% of the calculated mass of the zinc sulfide precipitate is added as a seed crystal, and a double decomposition reaction is carried out for 4.5 hours. After the reaction is completed, a slurry (the slurry includes zinc sulfide precipitate and alkali solution) is obtained.
[0125] S4. After the reaction is completed, the obtained slurry is centrifuged and separated by high-speed centrifuge to obtain zinc sulfide filter cake and filtrate;
[0126] The zinc sulfide filter cake is firstly alkaline washed once with a sodium hydroxide aqueous solution having a concentration of 28 wt% and 1 volume times the filtrate, and then washed twice with clean water having a volume of 11 volumes times the filtrate, to obtain a zinc sulfide crude product, an alkaline washing solution and a water washing solution;
[0127] After the carbonate is removed from the filtrate and the alkaline washing liquid by calcium hydroxide, they fully meet the chemical fiber pressing liquid standard (wherein the hydroxide concentration is 6.5 mol / L). One part is returned to the pulp pressing liquid process in the chemical fiber process, and the other part is returned to step S1 to replace the sodium hydroxide aqueous solution as the reaction solvent to dissolve zinc oxide.
[0128] After the washing liquid (containing a hydroxide concentration of 2.8 mol / L) is recovered, it is returned to the chemical fiber sulfur-containing waste gas absorption process to be used for chemical fiber to absorb hydrogen sulfide waste gas and prepare sodium hydrosulfide solution, thereby realizing the recycling of alkali solution and zero emission of the entire process.
[0129] The crude zinc sulfide was vacuum dried at 85°C for 1.5h, then heated to 120°C and dried for 1.5h, then placed in a tubular furnace, calcined at 500°C for 4.5h under nitrogen protection, and then ground to form a finished zinc sulfide product with a purity of 96%.
[0130] Example 6 A method for producing high-purity zinc sulfide using sodium hydrosulfide
[0131] This embodiment is a method for producing high-purity zinc sulfide using sodium hydrosulfide, and preparing nano-grade zinc sulfide, comprising the following steps:
[0132] S1. Dissolve industrial-grade zinc oxide in a 30wt% sodium hydroxide aqueous solution, stir and react at 60°C and 250r / min for 0.5h to generate a sodium zincate solution, wherein the mass percentage of the industrial-grade zinc oxide in the sodium hydroxide aqueous solution is 8.5wt%.
[0133] S2. In a sodium hydrosulfide solution with a concentration of 190 g / L, 203 g of sodium hydroxide solid is added per liter of sodium hydrosulfide solution to maintain a high alkaline environment to obtain an alkaline sodium sulfide solution. The sodium hydrosulfide solution is a by-product hydrogen sulfide waste gas treatment solution in the chemical fiber process.
[0134] S3. Under the control of a peristaltic metering pump, the molar ratio of sodium zincate in the sodium zincate solution to sodium sulfide in the alkaline sodium sulfide solution is 1:1, and the flow rates of both streams are 3 mL / min. The streams are added into a Y-type microchannel reactor in the form of impact inflow, and a double decomposition reaction is carried out at 60° C. and 2.2 MPa to obtain a slurry (the slurry includes zinc sulfide precipitate and alkali solution); wherein the left feed pipe 1 and the right feed pipe 2 of the Y-type microchannel reactor are both 280 cm in length and 1850 μm in diameter, and the Y-type angle between the left feed pipe 1 and the right feed pipe 2 is 80°.
[0135] S4. After the reaction is completed, the obtained slurry is centrifuged and separated by high-speed centrifuge to obtain zinc sulfide filter cake and filtrate;
[0136] The zinc sulfide filter cake is firstly alkali-washed once with a 30wt% sodium hydroxide aqueous solution of 1.2 times the volume of the filtrate, and then washed twice with clean water of 10 times the volume of the filtrate to obtain a zinc sulfide crude product, an alkali washing solution and a water washing solution;
[0137] After the carbonate is removed from the filtrate and the alkaline washing liquid by calcium hydroxide, they fully meet the chemical fiber pressing liquid standard (wherein the hydroxide concentration is 6.5 mol / L). One part is returned to the pulp pressing liquid process in the chemical fiber process, and the other part is returned to step S1 to replace the sodium hydroxide aqueous solution as the reaction solvent to dissolve zinc oxide.
[0138] After the washing liquid (containing a hydroxide concentration of 2.8 mol / L) is recovered, it is returned to the chemical fiber sulfur-containing waste gas absorption process to be used for chemical fiber to absorb hydrogen sulfide waste gas and prepare sodium hydrosulfide solution, thereby realizing the recycling of alkali solution and zero emission of the entire process.
[0139] The crude zinc sulfide was vacuum dried at 70°C for 1.8h, then heated to 115°C and dried for 1.5h, then placed in a tubular furnace, calcined at 600°C for 4h under nitrogen protection, and then ground to form a finished zinc sulfide product with a purity of 98%.
[0140] Example 7 A method for producing high-purity zinc sulfide using sodium hydrosulfide
[0141] This embodiment is a method for producing high-purity zinc sulfide using sodium hydrosulfide, and preparing nano-grade zinc sulfide, comprising the following steps:
[0142] S1. Dissolve industrial-grade zinc oxide in a 32wt% sodium hydroxide aqueous solution, stir and react at 80°C and 300r / min for 0.5h to generate a sodium zincate solution, wherein the mass percentage of the industrial-grade zinc oxide in the sodium hydroxide aqueous solution is 8wt%.
[0143] S2. In a sodium hydrosulfide solution with a concentration of 202 g / L, 234 g of sodium hydroxide solid is added per liter of sodium hydrosulfide solution to maintain a high alkaline environment to obtain an alkaline sodium sulfide solution. The sodium hydrosulfide solution is a by-product hydrogen sulfide waste gas treatment solution in the chemical fiber process.
[0144] S3. Under the control of a peristaltic metering pump, the molar ratio of sodium zincate in the sodium zincate solution to sodium sulfide in the alkaline sodium sulfide solution is 1:1.03, and the two flows are both 4 mL / min. They are added into a Y-type microchannel reactor in the form of impact inflow, and a double decomposition reaction is carried out at 60°C and 2 MPa to obtain a slurry (the slurry includes zinc sulfide precipitate and alkali solution); wherein, the left feed pipe 1 and the right feed pipe 2 of the Y-type microchannel reactor are both 280 cm in length and 1850 μm in diameter, and the Y-type angle between the left feed pipe 1 and the right feed pipe 2 is 70°.
[0145] S4. After the reaction is completed, the obtained slurry is centrifuged and separated by high-speed centrifuge to obtain zinc sulfide filter cake and filtrate;
[0146] The zinc sulfide filter cake is firstly alkaline washed once with a sodium hydroxide aqueous solution having a concentration of 32 wt% by volume of 1 times the filtrate, and then washed twice with clean water having a volume of 12 times the filtrate, to obtain a zinc sulfide crude product, an alkaline washing solution and a water washing solution;
[0147] After the carbonate is removed from the filtrate and the alkaline washing liquid by calcium hydroxide, they fully meet the chemical fiber pressing liquid standard (wherein the hydroxide concentration is 7 mol / L). One part is returned to the pulp pressing liquid process in the chemical fiber process, and the other part is returned to step S1 to replace the sodium hydroxide aqueous solution as the reaction solvent to dissolve zinc oxide.
[0148] After the washing liquid (containing a hydroxide concentration of 3 mol / L) is recovered, it is returned to the chemical fiber sulfur-containing waste gas absorption process to be used for chemical fiber to absorb hydrogen sulfide waste gas and prepare sodium hydrosulfide solution, thereby realizing the recycling of alkali solution and zero emission of the entire process.
[0149] The crude zinc sulfide was vacuum dried at 80°C for 2h, then heated to 120°C and dried for 2h, then placed in a tubular furnace, calcined at 400°C for 4h under nitrogen protection, and then ground to form a finished zinc sulfide product with a purity of 95%.
[0150] Example 8 A method for producing high-purity zinc sulfide using sodium hydrosulfide
[0151] This embodiment is a method for producing high-purity zinc sulfide using sodium hydrosulfide, and preparing nano-grade zinc sulfide, comprising the following steps:
[0152] S1. Dissolve industrial-grade zinc oxide in a 28 wt % sodium hydroxide aqueous solution, stir and react at 70° C. and 300 r / min for 0.5 h to generate a sodium zincate solution, wherein the mass percentage of the industrial-grade zinc oxide in the sodium hydroxide aqueous solution is 8.5 wt %.
[0153] S2. In a sodium hydrosulfide solution with a concentration of 200 g / L, 220 g of sodium hydroxide solid is added per liter of sodium hydrosulfide solution to maintain a high alkaline environment to obtain an alkaline sodium sulfide solution. The sodium hydrosulfide solution is a by-product hydrogen sulfide waste gas treatment solution in the chemical fiber process.
[0154] S3. Under the control of a peristaltic metering pump, the molar ratio of sodium zincate in the sodium zincate solution to sodium sulfide in the alkaline sodium sulfide solution is 1:1.02, and the two flows are both 4 mL / min, and are added into a Y-type microchannel reactor in the form of impact inflow, and a double decomposition reaction is carried out at 70°C and 2.5 MPa to obtain a slurry (the slurry includes zinc sulfide precipitate and alkali solution); wherein, the left feed pipe 1 and the right feed pipe 2 of the Y-type microchannel reactor are both 278 cm in length and 1845 μm in diameter, and the Y-type angle between the left feed pipe and the right feed pipe 2 is 60°.
[0155] S4. After the reaction is completed, the obtained slurry is centrifuged and separated by high-speed centrifuge to obtain zinc sulfide filter cake and filtrate;
[0156] The zinc sulfide filter cake is firstly alkaline washed once with a sodium hydroxide aqueous solution having a concentration of 28 wt% and 1 volume times the filtrate, and then washed twice with clean water having a volume of 11 volumes times the filtrate, to obtain a zinc sulfide crude product, an alkaline washing solution and a water washing solution;
[0157] After the carbonate is removed from the filtrate and the alkaline washing liquid by calcium hydroxide, they fully meet the chemical fiber pressing liquid standard (wherein the hydroxide concentration is 6.5 mol / L). One part is returned to the pulp pressing liquid process in the chemical fiber process, and the other part is returned to step S1 to replace the sodium hydroxide aqueous solution as the reaction solvent to dissolve zinc oxide.
[0158] After the washing liquid (containing a hydroxide concentration of 2.8 mol / L) is recovered, it is returned to the chemical fiber sulfur-containing waste gas absorption process to be used for chemical fiber to absorb hydrogen sulfide waste gas and prepare sodium hydrosulfide solution, thereby realizing the recycling of alkali solution and zero emission of the entire process.
[0159] The crude zinc sulfide was vacuum dried at 85°C for 1.5h, then heated to 120°C and dried for 1.5h, then placed in a tubular furnace, calcined at 500°C for 4.5h under nitrogen protection, and then ground to form a finished zinc sulfide product with a purity of 96%.
[0160] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A method for producing high-purity zinc sulfide using sodium hydrosulfide, characterized in that: The method comprises the following steps: carrying out double decomposition reaction of sodium hydrosulfide and zinc oxide under alkaline conditions, filtering / centrifuging after the reaction is completed, and purifying and calcining the obtained zinc sulfide filter cake to obtain a high-purity zinc sulfide finished product.
2. The method for producing high-purity zinc sulfide using sodium hydrosulfide according to claim 1, characterized in that: The filtrate from filtration / centrifugation and the washing liquid from the purification process are returned to the pulp pressing step or the sulfur-containing waste gas absorption step in the chemical fiber process according to different alkali concentrations.
3. The method for producing high-purity zinc sulfide using sodium hydrosulfide according to claim 1 or 2, characterized in that: The specific process of the method comprises the following steps: S1. Dissolve zinc oxide in sodium hydroxide aqueous solution to react and generate sodium zincate solution S2, adding sodium hydroxide to the sodium hydrosulfide solution to obtain an alkaline sodium sulfide solution; S3, sodium zincate solution and alkaline sodium sulfide solution are added to the reactor to carry out double decomposition reaction. After the reaction is completed, a slurry is obtained; wherein the slurry includes zinc sulfide precipitate; S4. After the reaction is completed, the obtained slurry is filtered / centrifuged to obtain a zinc sulfide filter cake and a filtrate; The zinc sulfide filter cake is firstly alkali-washed with a sodium hydroxide aqueous solution and then washed with water to obtain a zinc sulfide crude product, an alkali washing solution and a water washing solution; Part of the filtrate and the alkaline washing liquid is returned to the pulp pressing step in the chemical fiber process, and the other part is returned to step S1 to replace the sodium hydroxide aqueous solution as the reaction solvent to dissolve the zinc oxide; After the washing liquid is recovered, it is returned to the chemical fiber sulfur-containing waste gas absorption process to be used for chemical fiber to absorb hydrogen sulfide waste gas and prepare sodium hydrosulfide solution; The crude zinc sulfide is dried, calcined and ground to obtain zinc sulfide.
4. The method for producing high-purity zinc sulfide using sodium hydrosulfide according to claim 3, characterized in that: In step S1, the concentration of the sodium hydroxide aqueous solution is 25-32 wt %; In step S2, the sum of the amount of sodium hydroxide added to the sodium hydrosulfide solution and the sodium hydroxide released by the double decomposition reaction of sodium hydrosulfide and sodium zincate in step S3, with respect to the total mass of the sodium hydrosulfide solution, is 25-32 wt%.
5. The method for producing high-purity zinc sulfide using sodium hydrosulfide according to claim 3, characterized in that: In step S1, the mass percentage of industrial-grade zinc oxide in the sodium hydroxide aqueous solution is 8-9wt%.
6. The method for producing high-purity zinc sulfide using sodium hydrosulfide according to claim 3, characterized in that: In step S2, the sodium hydrosulfide solution is a liquid for treating hydrogen sulfide waste gas which is a byproduct in the chemical fiber process.
7. The method for producing high-purity zinc sulfide using sodium hydrosulfide according to claim 3, characterized in that: The particle size of zinc sulfide is controlled to be micron-sized by step S3. When the particle size of zinc sulfide is micron-sized, in step S3, the reactor is a hydrothermal reactor; The sodium zincate solution and the alkaline sodium sulfide solution are added into the reactor by double dropwise addition; The molar ratio of sodium zincate in the sodium zincate solution to sodium sulfide in the alkaline sodium sulfide solution is 1:1 to 1:1.03; After adding the sodium zincate solution and the alkaline sodium sulfide solution and before the double decomposition reaction, 11 to 30 wt% of the calculated zinc sulfide precipitate mass is added as a seed crystal; The double drop addition time is 30 to 60 minutes; The double decomposition reaction is carried out at a stirring speed of 200 to 300 r / min, a temperature of 60 to 80° C., and a time of more than 4 hours.
8. The method for producing high-purity zinc sulfide using sodium hydrosulfide according to claim 3, characterized in that: The particle size of zinc sulfide is controlled to be nanometer-level through step S3; when the particle size of zinc sulfide is nanometer-level, in step S3, the reactor is selected as a Y-type microchannel reactor; The Y-shaped microchannel reactor comprises a reaction chamber, a left feed pipe and a right feed pipe connected to the reaction chamber are fixed on the top of the reaction chamber in an inclined manner, and the left feed pipe and the right feed pipe are symmetrically arranged; The length of the left and right feed pipes is 280±2cm and the diameter is 1850±5μm; The Y-shaped angle between the left feed pipe and the right feed pipe is 60° to 90°; The total flow rate of adding sodium zincate solution and alkaline sodium sulfide solution is 3-5 mL / min, and the materials are added in a way of impacting the inflowing materials, and the pressure is 2-2.5 MPa; The temperature of the double decomposition reaction is 60-80°C; The molar ratio of sodium zincate in the sodium zincate solution to sodium sulfide in the alkaline sodium sulfide solution is 1:1 to 1:1.
03.
9. The method for producing high-purity zinc sulfide using sodium hydrosulfide according to claim 3, characterized in that: In step S4, during the alkali washing process, the amount of sodium hydroxide aqueous solution used is 1 to 1.5 times the volume of the filtrate, the concentration is 25 to 32 wt%, and the number of alkali washing is once; During the water washing process, the amount of clean water used is 10 to 12 times the volume of the filtrate, and the number of water washings is twice.
10. The method for producing high-purity zinc sulfide using sodium hydrosulfide according to claim 3, characterized in that: In step S1, the reaction temperature is 60-80°C and the stirring speed is 200-300 r / min; In step S4, drying is first performed at 60-85°C under vacuum for 1.5-2h, and then the temperature is raised to 110-120°C and dried for 1.5-2h; Calcination is carried out under nitrogen protection at 400-600°C for 2-4 hours.
Citation Information
Patent Citations
Method of preparing fine zinc sulfide through closed cycle
CN103288123B
A method for preparing pigment-grade zinc sulfide
CN113104883B